PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PERAWAT RUMAH SAKIT JIWA TAMPAN PROVINSI RIAU - Maulidia, Feny; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine the effect of the job statisfaction and organizational commitment on organizational citizenship behavior (ocb) of nurses at psychiatric hospital tampan riau province. Where two independent variables are proposed and one dependent variable. That is the job statisfaction and organizational commitment as independent variables and organizational citizenship behavior (ocb) as dependent variable. This research method is descriptive and quantitative by using program of SPSS 21, where sample used is nurses Non-PNS at Tampan Psychiatric Hospital Riau Province with responden counted 47 people. For sampling technique using census method. Techniques of data collection through questionnaires and interview. The result of the analysis using validity test, reliability test, determination test, simple regretion test, multiple linear regression test, t test, and f test, so that it can be seen that the job statisfaction has a significant effect on organizational citizenship behavior (ocb), that organizational commitment has a significant effect on organizational citizenship behavior (ocb), and that the job statisfaction and organizational commitment have a significant effect on organizational citizenship behavior (ocb).Keywords: The Job Statisfaction, Organizational Commitment, And Organizational Citizenship Behavior (Ocb)